Pengaruh Kebijakan Moneter Terhadap Pertumbuhan Ekonomi Di ASEAN-5 - Nadine Agatha Putri; Karsinah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
An important indicator of a country's success in achieving sustainable development goals is its economic growth rate. Monetary policy significantly influences growth by controlling interest rates, the money supply, foreign exchange reserves, and currency exchange rates. From 2004 to 2023, this study investigated the relationship between monetary policy and economic growth in the ASEAN-5 countries (Indonesia, Malaysia, the Philippines, Singapore, and Thailand) using panel data regression with a Fixed Effect Model approach. The findings show that economic growth is positively and significantly affected by interest rates, the money supply, foreign exchange reserves, and currency exchange rates. These findings emphasize the need for cooperation among the ASEAN-5 countries and the necessity of sound monetary policies to maintain development and economic stability.